COMPARATIVE ANALYSIS OF POTATO DISEASE LEAF IMAGE DENOISING METHODS BASED ON MATLAB - Zhang, Hongzhi (Techscience uz - Topical Issues of Technical Sciences, 2025)
Image denoising is one of the indispensable operations in image preprocessing, and the purpose of denoising is to effectively inhibit the excess noise components in the screen under the premise of ensuring that the original effective information of the image remains unchanged. In order to study the advantages and disadvantages of various denoising algorithms, this paper theoretically analyses Gaussian filtering, Mean filtering, Median filtering, Bilateral filtering and Wavelet filtering, and uses MATLAB to carry out simulation implementation and comparative analysis of various filtering and denoising effects on potato diseased leaf images.